2010
DOI: 10.1038/sj.bjc.6605634
|View full text |Cite
|
Sign up to set email alerts
|

Three dysregulated miRNAs control kallikrein 10 expression and cell proliferation in ovarian cancer

Abstract: BACKGROUND: Kallikrein-related peptidases (KLKs) are a family of serine proteases that have been shown to be dysregulated in several malignancies including ovarian cancer. The control of kallikrein genes and their physiological function in cancer is not well understood. We hypothesized that microRNAs (miRNAs) represent a novel mechanism for post-transcriptional control of KLK expression in cancer. METHODS: We first analysed miRNA expression in ovarian cancer in silico. A total of 98 miRNAs were reported to ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
0
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 77 publications
4
73
0
11
Order By: Relevance
“…miR-224 is reported to be overexpressed in various types of cancer (15)(16)(17)(18)(19)(20), and it plays critical roles in malignant phenotypes. Consistent with these previous observations, miR-224 was found to be upregulated in HepG2 cells in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-224 is reported to be overexpressed in various types of cancer (15)(16)(17)(18)(19)(20), and it plays critical roles in malignant phenotypes. Consistent with these previous observations, miR-224 was found to be upregulated in HepG2 cells in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The abnormal expression of miR-224 has been reported in several human cancers (15)(16)(17)(18)(19). Wang et al found that miR-224 is upregulated in HCC patients and HCC cell lines (20), and promotes HCC cell apoptosis by targeting the transcript expression levels of apoptosis inhibitor 5 (API-5).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, miR-142 was identified as the strongest signature associated with lymphocyte-specific gene expression and methylation across multiple cancer types in another study (9). Several recent cancer studies also supported the inhibitory effect on cell proliferation by miR-142-3p in pancreatic cancer (10) and miR-224 in ovarian cancer (11). The only miRNA that showed high expression in proliferative subtype and low expression in immunoreactive subtype is miR-218.…”
Section: Resultsmentioning
confidence: 72%
“…These results strongly suggested that miR-224 functioned as a tumour suppressor in PCa cells. Downregulation of miR-224 has also been reported in other types of human cancers, including ovarian, lung, and breast cancers, in addition to PCa [17][18][19][20][21]. Additionally, one study has shown that more aggressive PCa is associated with lower expression of miR-224 and that downregulation of miR-224 is associated with biochemical relapse [22].…”
Section: Discussionmentioning
confidence: 98%
“…Improved understanding of ncRNAs is necessary for continued progress in cancer research. MicroRNAs (miRNAs) are endogenous small ncRNA molecules (19)(20)(21)(22) bases in length) that regulate the expression of protein-coding genes by repressing translation or cleaving RNA transcripts in a sequencespecific manner [5]. A significant amount of evidence suggests that miRNAs are aberrantly expressed in many human cancers and play significant roles in the initiation, development, and metastasis of those cancers [6].…”
Section: Introductionmentioning
confidence: 99%